Liturgies of Livability or Liturgical Violence: What Kind of Space Is Christian Congregational Song Creating for LGBTQIA2S+ and Nonbinary People? - Budwey, Stephanie A. (Religions, 2023)
The liturgy is one of the most important places in which people are formed theologically through components such as prayers, music, visual art, and preaching. Yet, depending on the theology that is expressed, the liturgy can be a place that heals or harms. Because LGBTQIA2S+ and nonbinary people are often excluded and made invisible in Christian worship, this article focuses on the importance of Christian congregational song and how—drawing from Nathan Myrick’s work—it can be ethical for LGBTQIA2S+ and nonbinary people when it contributes to their flourishing. First is an articulation of a theology of “both/neither” which (1) acknowledges that LGBTQIA2S+ and nonbinary people exist, (2) is based on a sexually polymorphic reading of Genesis 1:27 and asserts that LGBTQIA2S+ and nonbinary people are made in God’s image, and (3) celebrates difference, diversity, and multiplicity. Next is a discussion of how enacting a theology of “both/neither” in the liturgy creates liturgies of livability for LGBTQIA2S+ and nonbinary people, whereas when it is not, it inflicts liturgical violence. This article concludes by exploring examples from Christian congregational song that support liturgies of livability through their expression of a theology of “both/neither.”